Atopic endotypes as a modulating factor for SARS-CoV-2 infection: mechanisms and implications. Issue 3 (June 2021) - Huntley, Kyle S.; Fine, Lauren; Bernstein, Jonathan A.
Abstract : Purpose of review: Asthma patients are typically at increased risk for severe outcomes from viral respiratory infections. However, asthma and atopy do not appear to be overrepresented comorbidities in COVID-19 patients, and hypotheses attempt to explain this observation. As COVID-19 continues to spread globally, it is imperative to understand how disease outcomes may be influenced in this population to guide patient care. Recent findings: Angiotensin converting enzyme 2 (ACE2) is the principal host cell receptor for SARS-CoV-2 entry and Transmembrane Protease Serine 2 (TMRSS2) is the main priming protease. Models have linked atopic endotypes to reductions in ACE2 and increases in TMRSS2 on respiratory epithelia. Epidemiologic and experimental findings imply alterations in ACE2 expression correlate with clinical COVID-19 disease, but limitations restrict the ability to draw direct conclusions. Summary: There is reasonable evidence to assert atopic endotypes modulate COVID-19 susceptibility, but it remains premature to classify this association as protective or deleterious. Asthma is a heterogeneous disease and epidemiologic studies should focus on investigating COVID-19 outcomes by underlying endotype. Direct experimental and clinical evidence is needed to draw definitive conclusions on how the complex interplay of ACE2 and TMRSS2 affect viral entry. Video abstract: https://www.dropbox.com/sh/9sfwqhz2h78sio3/AAB0JYd4MFzM5JjDFcYwz4CXa?dl=0